Illustrissima princeps, serenissima regina et domina clementissima: Epistles of Female Rulers and Noblewomen of GDL in the Late Fourteenth – the First Half of the Sixteenth Century - Keršienė, Dovilė (Senoji Lietuvos literatūra, 2014)
In this paper the author discusses Latin epistles of the female rulers and noblewomen of the Grand Duchy of Lithuania (GDL) of the late fourteenth to the first half of the sixteenth century. This epistolary legacy is analysed in the European context of female correspondence. As the research material was rather abundant, the paper consists of two parts. The first part focuses on the correspondence between women from the end of the fourteenth century to the first half of the fifteenth century, and the second part will address the epistles written from the second half of the fifteenth century to the first half of the sixteenth century. It should be noted that the amount of available sources for each period differs: sources extant from the late fourteenth to the early fifteenth century are considerably fewer than those from the late fifteenth century to the first half of the sixteenth century, and for this reasons this part of the paper does not aim at an exhaustive generalisation. Rather, it seeks to highlight the key moments in the development of female correspondence and the features of this correspondence during the period discussed. The author examines the frequency and extent (the circle of addressees) of female correspondence, its aims and themes (the types of letters), correspondence skills and opportunities, the style and expression of the epistles. For comparison purposes, instructions of letter-writing manuals on how a woman was supposed to write and how one was supposed to write to a woman was used.The sources of research include published Latin epistolary legacy of the grand duchesses of Lithuania, queens of Poland, and other noblewomen both from the Grand Duchy of Lithuania and other European countries. In some cases, not only letters written in other languages were used, but also fictional or literary epistolary texts related to the life and activities of the individuals discussed. They offer a better understanding of the space of the functioning of the epistles and of the peculiarities of communication between female rulers. The sources of this paper also include letters by male correspondents, because they contain information about the addressees, the attitude to them, the peculiarities of writing to women, the content of these epistles, and about possible and presumed amount of female correspondence that has not survived.The first infrequent letters of the female rulers, written down in Latin or German by the staff of the ducal or royal chancellery or by the clergymen, show that it was not yet a wide-spread phenomenon. However, the reconstruction method makes it possible to hypothesise that there were more letters written by women than the extant sources indicate. We can see from those few surviving sources of early correspondence between women that the circle of themes discussed in these letters was not yet wide. They reflect the topicalities of that particular period or the realities of the rulers’ daily life: political and diplomatic matters, events that had taken place in the rulers’ environment, recommendations, information, gratitude, apology, encouragement, reproach, and congratulation. The epistles of the female rulers were set out in line with the canon of ars dictaminis characteristic of the Middle Ages: their letters are written in a businesslike representative style and contain traditional rhetoric formalism. The lexicon used in the epistles corresponds to the status of the addresser. What is important is that the letters are more and more often addressed to the female ruler herself instead of passing something on or making a gift of something via her husband. Still, when a woman’s belonging to a certain social status or a stratum in a family hierarchy is referred to in the epistles, the general attitude of those times – that a woman must ‘belong’ to someone – is prominent: she is addressed as a wife, a widow, or a sister. It should be emphasised that female letters of the late fourteenth to the early sixteenth century were hardly ever entirely private. In the epistles of a female ruler, we will not find many intimate details because the specifics of her status and correspondence, and the level of literacy did not provide extensive opportunities for the existence of exclusively private correspondence: even when a letter is addressed to a close relative or a beloved, or when it conveyed warm feelings, the distance was maintained.
Keywords: -